Implementation of 5S in Improving of Palm Oil Mill Working Environment - Syahputri, Khalida; Rizkya, Indah; Meilina Sari, Rahmi; Lo, Albert (TALENTA Publisher, 2023)
A work environment describes a place for employees affect them to do their tasks. A good work environment will certainly make employees do and spend all their energy and mind to work optimally. A comfortable feeling of the work environment can reduce boredom at work. This comfort feelings have an impact on increasing motivation and producing employee job satisfaction. The condition of the working environment in palm oil industry is currently classified as messy where there are still some tools scattered on the factory floor, there is mud and slippery puddles in various places such as floors or stairs. Conditions like this certainly need to be repaired immediately to avoid the risk of work accidents and increase employees' comfortable. Improvement of working environment conditions can be done by various methods, one of the methods is 5S method. 5S spelling as (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) is one of the effective tool in management to improve the work culture of workers and the conditions of the work environment in a factory. Based on the evaluation results, the evaluation categories of 5S implementations are Seiri of 16 score, Seiton of 16 score, Seiso of 9 score, Seiketsu of 8 score, Shitsuke of 7 score. The results of this total score show the 5S value of palm oil mill is in the average score of 56 total score.